Brief Report: Cartilage Thickness Change as an Imaging Biomarker of Knee Osteoarthritis Progression: Data From the Foundation for the National Institutes of Health Osteoarthritis Biomarkers Consortium - Eckstein, Felix; Collins, J. E.; Nevitt, M. C.; Lynch, J. A.; Kraus, V. B.; Katz, J. N.; Losina, E.; Wirth, Wolfgang; Guermazi, A.; Roemer, Frank; Hunter, D. J. (Arthritis and Rheumatology, 2015)
To investigate the association of cartilage thickness change over 24 months, as determined by magnetic resonance imaging (MRI), with knee osteoarthritis (OA) progression at 24-48 months.This nested case-control study included 600 knees with a baseline Kellgren/Lawrence (K/L) grade of 1-3 from 600 Osteoarthritis Initiative (OAI) participants. Case knees (n = 194) had both medial tibiofemoral radiographic joint space loss (>=0.7 mm) and a persistent increase in the Western Ontario and McMaster Universities Osteoarthritis Index pain score (>=9 on a 0-100 scale) 24-48 months from baseline. Control knees (n = 406) included 200 with neither radiographic nor pain progression, 103 with radiographic progression only, and 103 with pain progression only. Medial and lateral femorotibial cartilage was segmented from sagittal 3T MRIs at baseline, 12 months, and 24 months. Logistic regression was used to assess the association of change in cartilage thickness, with a focus on the central medial femorotibial compartment, and OA progression.Central medial femorotibial compartment thickness loss was significantly associated with case status, with an odds ratio (OR) of 1.9 (95% confidence interval [95% CI] 1.6-2.3) (P < 0.0001). Association with case status reached P < 0.05 for both the central femur (OR 1.8 [95% CI 1.5-2.2]) and the central tibia (OR 1.6 [95% CI 1.3-1.9]). Lateral femorotibial compartment cartilage thickness loss, in contrast, was not significantly associated with case status. A reduction in central medial femorotibial compartment cartilage thickness was strongly associated with radiographic progression (OR 4.0 [95% CI 2.9-5.3]; P < 0.0001) and only weakly associated with pain progression (OR 1.3 [95% CI 1.1-1.6]; P < 0.01).Our findings indicate that loss of medial femorotibial cartilage thickness over 24 months is associated with the combination of radiographic and pain progression in the knee, with a stronger association for radiographic progression.
EVALuna2:14522